Novel triple coaxial system to navigate 9 French balloon guiding catheter into common carotid artery. Issue 6 (December 2020) - Yasuda, Ryuta; Toma, Naoki; Suzuki, Yume; Miura, Yoichi; Shiba, Masato; Suzuki, Hidenori
Background: It is often hard to navigate a 9 French (F) balloon guiding catheter in patients with type III or bovine aortic arch. Also, a common carotid artery stenosis is challenging, because a guidewire cannot be advanced distally. We developed the combination of a 4F Simmons-type catheter and a 6F distal access catheter as a coaxial inner catheter to navigate a 9F balloon guiding catheter to overcome these difficulties. Materials and methods: Medical record at our institution was retrospectively reviewed and carotid artery stenting cases in which the 4F Simmons-6F distal access catheter system was employed as a coaxial catheter to navigate a 9F balloon guiding catheter were identified. To construct this system, a 4F 145 cm SY3 (Hanako Medical, Saitama, Japan) and a 6F 118 cm Cerulean DD6 (Medikit Co. Ltd., Tokyo, Japan) were usually employed. A rotating hemostatic valve should be as short as possible and was attached to only a 9F balloon guiding catheter. The length of a 0.035-in. guidewire needed to be 180 cm or longer. Results: During the study period, 106 carotid artery stenting cases were identified. Of these, this system was employed in 29 cases that included 5 cases with a steno-occlusive lesion at common carotid artery/external carotid artery, 10 with type III or bovine arch, and 11 harboring both. In all the cases, a 9F balloon guiding catheter was successfully navigated. Conclusion: The 4F Simmons-6F distal access catheter system was useful in navigating a 9F balloon guiding catheter in patients with a common carotid artery stenosis, an external carotid artery occlusion, and an in-stent restenosis, especially when they also harbored type III or bovine aortic arch.